Clinicopathological features and genomic profiles of a group of secretory breast carcinomas in which progressive cases have more complex genomic features - Ting Lei; Yuyan Yang; Yongqiang Shi; Xu Deng; Yan Peng; Hui Wang; Tongbing Chen (BMC, 2022)
Abstract Background Secretory breast carcinoma (SBC) is a rare malignant breast neoplasm with distinct histological features, including solid, microcystic, tubular, and rarely papillary structures, traditionally characterized by a t (12;15) (p13:q25) translocation, which usually leads to ETV6-NTRK3 fusion, suggesting an early event in tumorigenesis. Due to the rarity of this disease, very few genome sequencing studies have been performed on a series of cases, especially progressive cases. Methods Seven lesions from 5 patients diagnosed at the Third Affiliated Hospital of Soochow University from 2007 to 2021 were included. Clinicopathological features and prognosis/survival data were collected. Next-generation DNA sequencing was performed on six of the seven lesions. Results In total, 3/7 (42.9%) lesions demonstrated estrogen receptor (ER) expression, including weak, moderate to strong staining, and no lesion demonstrated progesterone receptor (PR) expression. There were no cases of human epidermal growth factor (HER2) overexpression, and the Ki-67 index was low. S-100 and pan-TRK protein were diffusely positively expressed in all cases. All lesions were characterized by a t(12;15) (p13:q25) translocation, leading to ETV6-NTRK3 fusion confirmed by fluorescence in situ hybridization (FISH). The sequencing results showed that ETV6-NTRK3 fusion was the main driver of early tumorigenesis, while SBC with invasive biological behavior had more complex genomic variation in which TERT promoter mutation was detected. Conclusions Immunohistochemical staining of a biomarker panel, including ER, PR, HER2, Ki-67, S-100 and pan-TRK, can be used as an auxiliary diagnostic tool, and FISH detection can be used as a diagnostic tool. ETV6-NTRK3 gene fusion involving multiple sites may drive tumorigenesis, while mutations in the TERT promoter region may be a factor driving tumor progression.